New and little-known gnathiid isopod crustaceans (Cymothoida) from the northern Great Barrier Reef and the Coral Sea - Svavarsson, Jörundur; Bruce, Niel L. (Zootaxa, 2012)
Ten species of Gnathiidae (Crustacea, Isopoda, Cymothoida) including six new species, are reported from Lizard Islandand nearby reefs, northern Great Barrier Reef and reefs of the Coral Sea (Chesterfield Reefs, Mellish Reef and MarionReef): Gnathia wistari sp. nov. (Lizard Island region and Capricorn Group, southern Great Barrier Reef), Gnathia coral-maris sp. nov. (Mellish Reef), Gnathia varanus sp. nov. (Lizard Island group), Gnathia marionis sp. nov. (Marion Reef),Gnathia hamletgast sp. nov. (Chesterfield Reefs) and Elaphognathia australis sp. nov. (Chesterfield Reefs). New locali-ties are reported for four other species: Gnathia aureamaculosa Ferreira and Smit, 2009 and Gnathia masca Farquharsonand Smit, 2012 from Lizard Island and nearby reefs; Gnathia falcipenis Holdich and Harrison, 1980 and Gnathia variobranchia Holdich and Harrison, 1980 from Lizard Island, Wistari Reef, Heron Island and Chesterfields Reefs.